Global burden of early-onset pancreatic cancer attributable to metabolic risks from 1990 to 2021, and projections to 2030 - Fang, Yingjin; Xu, Yile; Xing, Faliang; Zhang, Weixin; Liang, Chen; Meng, Qingcai; Li, Jialin; Xu, Jin; Wang, Wei; Qin, Yi; Yu, Xianjun; Zhang, Bo (Frontiers in Oncology, 2025)
This study, based on the Global Burden of Disease (GBD) 2021 data, systematically analyzed the changes in the disease burden of early-onset pancreatic cancer (EOPC) attributable to high fasting plasma glucose (HFPG) and high body mass index (HBMI) among the global population aged 15–49 years from 1990 to 2021 and predicted the mortality trends up to 2030. The results show that metabolic risk factors have a significant impact on EOPC: In 2021, the global deaths from EOPC attributable to HFPG reached 3,334 cases, 2.3 times higher than in 1990 with the age-standardized mortality rate (ASMR) and age-standardized disability rate (ASDR) had average annual growth rates of 1.50% and 1.47%. The ASMR and ASDR growth rates attributable to HBMI were even higher (1.69% and 1.76%). The steepest ASMR increases occurred in low-middle socio-demographic index (SDI) regions with an average annual growth of 2.86%), while the highest absolute burdens were observed in East Asia, high-income North America, and Western Europe. Bayesian age-period-cohort (BAPC) model predictions indicate that by 2030, the ASMR related to HBMI will continue to rise in both sexes (from 0.90 to 1.65 per 100,000 in males and from 1.43 to 1.93 per 100,000 in females), and the HBMI may exert a greater impact on females than HFPG. The study reveals the “double burden” phenomenon of metabolic risks: high-SDI regions have a high absolute burden due to the accumulation of long-term metabolic diseases, while low-middle SDI regions experience significant growth rates due to rapid urbanization and a lack of medical resources. Gender difference analysis shows that males generally have a higher ASMR than females, but the upward trend of metabolic-related mortality rates in females is more severe. The interaction between behavioral pattern changes in young people and metabolic abnormalities further exacerbates the risk. This study provides temporospatial evidence for the prevention and control of global EOPC, emphasizing the need to strengthen interventions for metabolic diseases in middle-and low-income regions, optimize the allocation of medical resources, and prioritize gender- and youth-specific interventions to curb the global spread of this aggressive cancer.